Discussion about the role of teacher authority when making a transition into creative problem-solving in mathematics - Andresen, Mette; Dahl, Bettina (Acta Didactica Norden, 2023)
When introducing a new kind of teaching activity into the classroom, the teacher cannot foresee whether the students will accept it or not. Even when the students do, there is a risk, that they might be neither able nor willing to adopt all aspects of it. The teacher, then, faces a dilemma between, on the one hand, trying to win the students over to this new activity, and on the other hand, exerting an authority that may overrule the students’ own initiatives and ideas and which includes the potential danger of “losing” the students. In this article, we present a retrospect re-analysis of an older case where the teacher faces such a dilemma. After analysing video recordings and interviews with the teacher through the lenses of authority, we discuss how the teacher handled this dilemma. Here we take a participationist’s perspective and apply theories on authority and positioning. From this perspective, we argue that the teacher’s choice of not clearly exerting his authority leaves the students in doubt about whether they fulfilled the requests. We conclude that in the present case a “too nice” atmosphere in the Norwegian classroom had obstructed the teacher’s desire to implement a profound change. We come to the general conclusion that teachers need to feel comfortable with being assertive and being willing to exercise authority for the implementation of a new teaching activity, including that of creative problem-solving.